The ransomware hunting team : a band of misfits' improbable crusade to save the world from cybercrime - Dudley, Renee, 1985-; Golden, Daniel, 1957- (Farrar, Straus and Giroux, 2022)
"The story of a band of volunteer cybersecurity experts who use their computer skills to crack ransomware and help victims of cybercrime"--